Students' needs and conditions for receiving information: Evidence from Vietnamese universities today - Huyen, Nguyen Thị (Edelweiss Applied Science and Technology, 2025)
Given the expansion of Vietnam’s digital higher education landscape, it has become imperative to understand the factors contributing to students’ capacity to effectively receive and interpret academic information. This study develops and empirically tests a multidimensional model of Information Reception Effectiveness (IRE) using data collected from a survey distributed to 300 undergraduate students in Hanoi and Ho Chi Minh City. We employed multiple linear regression analysis to better understand how seven predictors (digital accessibility, information literacy, motivational orientation, socioeconomic background, institutional support, psychological readiness, and learning engagement) explain IRE. The model was statistically significant; F(7, 292) = 150.17, p < 0.001. The model explained 78.3% of the variability in IRE (R² = 0.783, Adjusted R² = 0.777). All predictors were positively and significantly associated with the outcome measure (p < 0.001). The two unstandardized predictors with the greatest effects were information literacy (β = 0.156) and digital accessibility (β = 0.145), followed closely by socioeconomic background (β = 0.139) and institutional support (β = 0.126). Notably, psychological and behavioral characteristics also made substantial contributions to IRE, including psychological readiness (β = 0.111), motivational orientation (β = 0.109), and learning engagement (β = 0.104). The results highlight the need for comprehensive strategies based on a combination of improved digital access, increased institutional capacity, and enhanced student readiness as they engage with digitally-based learning.